2018
DOI: 10.1111/echo.13858
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular structural alterations are accompanied by subclinical systolic dysfunction in type 2 diabetes mellitus patients with concomitant hyperlipidemia: An analysis based on 3D speckle tracking echocardiography

Abstract: The combination of conventional echocardiography and 3DSTE could detect subclinical LV abnormalities in T2DM patients with or without hyperlipidemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
(47 reference statements)
2
5
0
2
Order By: Relevance
“…Most of the I 2 characteristics improved compared with the whole‐group analyses, most substantially in 3D GAS in patients with diabetes mellitus from 68% to 49%, followed by 3D GLS from 78% to 69%. Forest plots of 3D GLS in the group of patients with diabetes mellitus and the control group as well as MD of our subgroup analysis are shown in Figure 3 , 10 , 11 , 12 , 13 , 15 , 18 , 19 , 20 , 21 which was consistent with the main meta‐analysis. The other results of subgroup analysis in each group and MD of each strain value were also consistent with our main meta‐analysis (Figures S8 through S10 ).…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…Most of the I 2 characteristics improved compared with the whole‐group analyses, most substantially in 3D GAS in patients with diabetes mellitus from 68% to 49%, followed by 3D GLS from 78% to 69%. Forest plots of 3D GLS in the group of patients with diabetes mellitus and the control group as well as MD of our subgroup analysis are shown in Figure 3 , 10 , 11 , 12 , 13 , 15 , 18 , 19 , 20 , 21 which was consistent with the main meta‐analysis. The other results of subgroup analysis in each group and MD of each strain value were also consistent with our main meta‐analysis (Figures S8 through S10 ).…”
Section: Resultssupporting
confidence: 85%
“…Forest plots of GLS MD in the group of patients with diabetes mellitus and the control group are shown in Figure 2 . 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 3D GCS, GRS, and GAS were also lower in patients with diabetes mellitus. However, GCS had a medium effect size, and GRS and GAS had a small effect size (Table 5 , Figures S1 through S3 ).…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…With the occurrence of microvascular complications, myocardial damage can be serious and even lead to cell necrosis or myocardial ischemia, for example, and, at this point, there will be myocardial stiffness and ventricular remodeling. These pathological changes (Rijzewijk et al, 2008;van den Bergh et al, 2008) and the changing trend of the strain parameters were basically similar to the findings of previous studies (Ernande et al, 2010;Li et al, 2014;Sugimoto et al, 2017;Lin et al, 2018;Mirea et al, 2018;Wang et al, 2018). It can be concluded that strain parameters, such as GLS, are very sensitive markers of LV systolic function, much more so than LVEF (Hung et al, 2010;Park et al, 2018;Santos-Gallego et al, 2019).…”
Section: Discussionsupporting
confidence: 88%